PENGARUH CAKUPAN IMUNISASI CAMPAK TERHADAP INCIDENCE RATE PENYAKIT CAMPAK DI INDONESIA TAHUN 2016 - Satriya Wijaya (Universitas Nahdlatul Ulama Surabaya, 2018)
Immunization has proven to be one of the most important public health efforts. The immunization program has shown remarkable success and is a very cost-effective effort in preventing infectious diseases (MOH, 2003). Immunization has also saved so many lives compared to other public health efforts. Very important role of measles immunization in reducing child mortality, so measles immunization become one of indicator in achieving fourth goal of MDGs that is decrease child mortality rate. In this case, what is seen is the proportion of one-year-old children who get measles immunization (WHO, 2014 in the Ministry of Health RI, 2014).